Experimental infections of sand flies and geckos with Leishmania (Sauroleishmania) adleri and Leishmania (S.) hoogstraali - Ticha, Lucie; Sadlova, Jovana; Bates, Paul; Volf, Petr (Parasites & vectors, 2022)
BACKGROUND: Species belonging to the subgenus Sauroleishmania are parasites of reptiles, and traditionally considered to be non-pathogenic to mammals. Knowledge of the development of these parasites in sand flies and their mechanism of transmission is currently lacking. The main aim of this study was to test the susceptibility of various sand fly species to infection by two Sauroleishmania species, focusing on the localization of parasites in the sand fly intestinal tract. METHODS: The development of Leishmania (Sauroleishmania [S.]) adleri and Leishmania (S.) hoogstraali was studied in six sand fly species (Phlebotomus orientalis, P. argentipes, P. sergenti, P. papatasi, P. duboscqi, Sergentomyia schwetzi). Sand flies were fed through a chick-skin membrane on blood containing Sauroleishmania promastigotes, and they were dissected at various time intervals post blood meal (PBM). Guts were examined microscopically for the presence of parasites, and the intensity and localizations of infections were recorded. Morphological forms of both Sauroleishmania species developing in P. orientalis were analyzed. Experimental infections of geckos using sand fly-derived promastigotes were also performed, and the reptiles were repeatedly examined for Sauroleishmania infection by xenodiagnosis and PCR analysis. RESULTS: High infection rates for both Sauroleishmania species were observed in P. orientalis and P. argentipes, with the parasites migrating anteriorly and undergoing a peripylarian type of development, including colonization of the stomodeal valve. Conversely, the development of L. (S.) adleri in P. sergenti, P. papatasi and Se. schwetzi was restricted to the sand fly hindgut (hypopylarian type of development). Five morphological forms were distinguished for both Sauroleishmania species developing in P. orientalis. All experimentally infected geckos scored negative for Sauroleishmania based on xenodiagnosis and molecular analysis. CONCLUSIONS: The results showed that Sauroleishmania promastigotes can undergo either a peripylarian or hypopylarian type of development in the sand fly intestinal tract, depending on the sand fly species infected. We demonstrated that P. argentipes and P. orientalis, two sand fly species known as permissive vectors for mammalian parasites of subgenus Leishmania, are also highly susceptible to Sauroleishmania as the parasites developed mature late-stage infections, including colonization of the sand fly stomodeal valve. Thus, the role of Phlebotomus sand flies in transmission of Sauroleishmania should be reconsidered and further investigated.
Keywords: Lizards; xenodiagnóza; Psychodidae; Geckos; Sand flies; Sergentomyia; ještěři; zvířata; Mammals; Xenodiagnosis; Leishmaniasis; Phlebotomus; savci; Sauroleishmania; Leishmania; Animals